(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2016)
هدفت الدراسة إلى تسليط الضوء على الصكوك الإسلامية باعتبارها منتجاً إسلامياً بديلاً عن الأوراق المالية التقليدية، وإلى إبراز دورها في توفير السيولة اللازمة للمصارف الإسلامية لتمويل مشروعاتها، وإلى استعراض المخاطر التي تتعرض لها المصارف الإسلامية في تعاملها مع الصكوك الإسلامية إصداراً وتداولاً، تمت الدراسة على البنك الإسلامي للتنمية في جدة، كدراسة حالة، حيث تم إجراء المقابلات الشخصية وتوزيع الاستبانة على الموظفين المعنيين بالتعامل مع الصكوك في المصرف (محل الدراسة)، وخلصت الدراسة إلى أن الصكوك الإسلامية من المنتجات منخفضة المخاطر، كما أن مخاطر الإصدار والتداول هي واحدة للحالة المدروسة. This study aimed to shed light on Islamic Sukuk as an alternative to traditional securities Islamic product, and to highlight their role in providing the necessary liquidity for Islamic banks to finance their projects, as risks to Islamic banks from dealing with Islamic Sukuk review, study was performed on the Islamic Bank development in Jeddah, as a case study, where he has been conducting personal interviews and distribute the questionnaire to the staff involved in dealing with the Sukuk in the Islamic Development Bank, and the study concluded that the Islamic Sukuk of low-risk products, as that version and trading risk is the same for the case studied.